Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So the question was basically " Suppose that there are n teams in a rugby league competition. Every team A plays every other team B twice, once at the home ground for team A, and the other time at the home ground for team B."

2(n 1) + 2(n 2) + 2(n 3) + : : : + 6 + 4 + 2 is given

a) Write the expression in summation notation. b) Use mathematical induction to prove it, n>=2

So I got this expression for (a) n^Sigma(i=1) = (2(n-i)) where n is the number of teams

Part B

Proof:

Let P(n) denote the sequence n^Sigma(i=1)=2(n-i) and n≥2

Consider P (2) n^Sigma(i=1)=2(n-i) =2(2-1)=2 ∴it is true when n=2

We will now assume it is true for P(k)

k^Sigma(i=1)=2(k-i) for some integer k ≥2

Consider P(k+1)

k+1^Sigma(i=1)=2(k+1-i) for some integer k ≥2

P(k+1)=2(k-1)+2(k-2)+2(k-3)+⋯+2(k-i)+2(k+1-1)

Since we have assumed that P(k) is true.

So we know: P(k+1)=P(k)+(k+1)

ANSWER i cant answer my own question for 8hrs so here it is:

P(n)=n^2-n

P(K+1)=P(k)+2((k+1)-1)

P(K+1)=〖(k〗^2-k)+2(k+1)-2

P(K+1)=〖(k〗^2-k)+2(k+1)-2

P(K+1)=〖(k〗^2-k)+2k+2-2

P(K+1)=〖(k〗^2-k)+2k

P(K+1)=〖(k〗^2+k)

P(K+1)=(k+1)^2-(k+1)

Therefore under induction the sequence has been proven.

Thanks to @P..

share|improve this question
    
The answer for part (a) is correct. But for part (b) what are you trying to prove? What do you think $P(k)$ equals to? Hint: Arithmetic progression. –  P.. Apr 24 '13 at 6:16
    
well P(k)=2(k-i)=2k-2i. Know P(K+1)=P(k)+k+1= 2(k-i)+(k+1) which brings me right back to where i am. –  Ghozt Apr 24 '13 at 6:19
    
So can you tell me from your expression what $P(3)$, or $P(5)$ is? The answer should be a number. –  P.. Apr 24 '13 at 6:20
    
@P.. So is P(k)=K^2-k? –  Ghozt Apr 24 '13 at 7:18
    
Yes! Now try to prove it using induction. If you need any help let me know. –  P.. Apr 24 '13 at 7:21
show 1 more comment

1 Answer

The OP edited in an answer to his/her post; I'm copying it here so the question isn't "unanswered."

$P(n)=n^2-n$

$P(k+1)=P(k)+2((k+1)-1)$

$P(k+1)= (k^2-k)+2(k+1)-2$

$P(k+1)=(k^2-k)+2(k+1)-2$

$P(k+1)=(k^2-k)+2k+2-2$

$P(k+1)=(k^2-k)+2k$

$P(k+1)=(k^2+k)$

$P(k+1)=(k+1)^2-(k+1)$

Therefore under induction the sequence has been proven.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.